Three Flavan-3-ols from Artocarpus reticulates - Sjamsul Arifin Achmad; Murniana Murniana; Silvester Sigit Udjiana; Euis Holisotan Hakim; Lukman Makmur; Norio Aimi (Institute for Research and Community Services (LPPM) ITB, 1998)
Tiga senyawa turunan flavan-3-ol, yakni afzelekin-3-O-a-L-ramnosida (1), katekin (2), dan afzelekin (3), telah ditemukan pada kulit batang dan kulit akar tumbuhan Artocarpus reticulatus Miq. (Moraceae), suatu tumbuhan langka yang berasal dari Sulawesi dan endemik untuk Indonesia, serta dikenal dengan nama daerah maumbi. Struktur molekul ketiga senyawa tersebut telah ditetapkan berdasarkan data fisika dan spektroskopi. Three Flavan-3-ols from Artocarpus reticulatesThree flavan-3-ol derivatives, namely afzelechin-3-O-Î±-L-rhamnoside (1), catechin (2) and afzelechin (3), were isolated from the tree and the root barks of Artocarpus reticulaltus Miq. (Moraceae), a rare species found in Sulawesi and endemic to lndonesia, locally known as maumbi. The structures of all these compounds were elucidated based on physical and spectroscopic data.